Antibacterial Effects Of Phomopsidione Isolated From Diaporthe Fraxini Against Methicillin-resistant Staphylococcus Aureus (Mrsa) With Gene Expression And Metabolomics Profiling - Wei, Yee Min (2023)
The rising prevalence of multidrug-resistant (MDR) pathogens has contributed to a high mortality rate due to overuse and misuse of antibiotics. Among the MDR pathogens, methicillin-resistant Staphylococcus aureus (MRSA) is the most threatening and poses the greatest impact on public health. Thus far, many bioactive ketone derivatives have been reported as anti-MRSA agents. Phomopsidione (C7H10O4), a bioactive ketone derivative isolated from Diaporthe fraxini, has previously demonstrated antibacterial effects. The present study was aimed to investigate the antibacterial and anti-biofilm effects of phomopsidione against MRSA and determine the phomopsidione-mediated modulation in virulence factors production. Additionally, the changes in gene expression and metabolites profile of MRSA in response to phomopsidione were examined. In broth microdilution assay, phomopsidione exhibited significant inhibitory activity against MRSA with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of 62.5 and 500.00 μg/mL, respectively. In crystal violet biofilm assay, phomopsidione inhibited and eradicated biofilm in a concentration-dependent manner. Phomopsidione showed significant reduction in the virulence factors production of MRSA at MIC and MBC when assessed using quantification of extracellular polymeric substances (EPS), catalase and lipase production assays.